2017
DOI: 10.1371/journal.pone.0175430
|View full text |Cite
|
Sign up to set email alerts
|

Elements including metals in the atomizer and aerosol of disposable electronic cigarettes and electronic hookahs

Abstract: ObjectiveOur purpose was to quantify 36 inorganic chemical elements in aerosols from disposable electronic cigarettes (ECs) and electronic hookahs (EHs), examine the effect of puffing topography on elements in aerosols, and identify the source of the elements.MethodsThirty-six inorganic chemical elements and their concentrations in EC/EH aerosols were determined using inductively coupled plasma optical emission spectroscopy, and their source was identified by analyzing disassembled atomizers using scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
167
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(182 citation statements)
references
References 24 publications
4
167
1
1
Order By: Relevance
“…As indicated, most e-liquids sampled from cartridges or from tanks or open wicks that were in contact with the coil had higher metal/metalloid levels in comparison with levels in e-liquids sampled from the bottle. Numerous studies have shown that e-liquids in contact with heating coils like nichrome or kanthal (Olmedo et al 2018;Palazzolo et al 2017;Williams et al 2013Williams et al , 2015Williams et al , 2017Zhao et al 2018) facilitate leaching of metals/metalloids into the liquid present in the tank or cartomizer. A recently published study showed that metals (Cu, Ag, Ni, Si, Ca, Al, Mn, Zn, and Sn) were used in various device components, such as thick wires, wicks, sheaths, and joints (Williams et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As indicated, most e-liquids sampled from cartridges or from tanks or open wicks that were in contact with the coil had higher metal/metalloid levels in comparison with levels in e-liquids sampled from the bottle. Numerous studies have shown that e-liquids in contact with heating coils like nichrome or kanthal (Olmedo et al 2018;Palazzolo et al 2017;Williams et al 2013Williams et al , 2015Williams et al , 2017Zhao et al 2018) facilitate leaching of metals/metalloids into the liquid present in the tank or cartomizer. A recently published study showed that metals (Cu, Ag, Ni, Si, Ca, Al, Mn, Zn, and Sn) were used in various device components, such as thick wires, wicks, sheaths, and joints (Williams et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…The total SD was estimated because it accounts for the SD within the groups as well as among the groups (Sharma 2006). For some studies, there were insufficient data to estimate the SD because only means were reported, with no estimation of variability around those point estimates (Beauval et al 2017;Dunbar et al 2018;Margham et al 2016;Palazzolo et al 2017;Song et al 2018;Williams et al 2013;Williams et al 2017;Zhao et al 2018). The study by Olmedo et al (2018) reported medians instead of means (SDs) in the original publication, but we calculated them directly from the original data.…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Although, here we have provided data on the chemical content of E‐cig aerosols, we mainly focused on the organic chemical constituents, with emphasis on those that are known to be present in cigarette smoke. E‐cig aerosols also contain metal nanoparticles that are a potential source of toxicity and oxidative potential (Williams, Bozhilov, Ghai, & Talbot, ). This is a factor that should be considered in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%